NVivo Based Al-Quranic Features in Students for Autism Therapy - Wiliams, Alexander; Faturahman, Adam; Rahardja, Untung; Oganda, Fitra Putri; Pangestu, Anggit Panji (Pandawan, 2021)
In 2018, according to data from the CDC in America, it is estimated that 1 in 59 children prevalence (incidence rate) of children have Autism Spectrum Disorder, compared to 2014, which is 1 in 68 children increased by 15%. The average boy often experiences unique symptoms, the problem is on the spectrum of neural development and can affect all sorts of aspects of learning, although many researchers focus on aspects of related issues but are measured to lack emphasis. So it is done on the learning of problems associated with religious education, read the Qur'an lovingly and also pray (?al??). Non-Arab speakers with autism, this study aims to characterize the natural characteristics displayed by a special student (autistic) in reading the Quran. To provide the same opportunity in carrying out their religious obligations, an 8-year-old boy from Malay with autism is already high, for a month with a session conducted three times the program was chosen as the subject. At least during the six months of Al-Quran lessons and he was able to communicate orally in class. NVivo software is useful for this analysis and it was found that every experimental session was recorded by audio by a digital camera and a digital camera visual voice recorder. the first chapter test includes reading the Quran (al-Fatihah) using five different types: (a) Malay Translation, (b and c) the complete set of chapters in Uthmani and Rasm Qiyasi races respectively, and ( d and e) sets of disorganized and incomplete chapters in Uthmani rasm. Research Autistic individuals for the selection of appropriate recommended reading materials. Teachers and parents for effectiveness in studying the Quran need to be considered, This identifies the features that have been shown during the lessons of the Quran.